PENGARUH LATIHAN GERAK PINGGUL (STRETCHING) TERHADAP TINGKAT NYERI PUNGGUNG BAWAH PADA LANSIA DI DESA MEKAR SARI KECAMATAN DELITUA KABUPATEN DELI SERDANG - Lili Suryani Tumanggor; Daniel Suranta Ginting (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2020)
Stretching is one form of therapy needed to lengthen muscles that increase shortening or increase elasticity and enlarge muscles. Maintain muscles at their natural length and can maintain their function properly. This type of research uses a pre-experimental research design with the design of a pretest-posttest group that is there is no comparison group (control), but the first observation (pretest) has been made that allows research that can improve the changes produced after the study. The sample is part of the population to be excluded or part of the characteristics possessed by the population. How to take a sample by taking the entire sample of participation into a sample (total sampling) of 20 people. The decisive variable in this study is the rate of return of the lower back in the elderly. This research uses paired t statistical test with α <0.05. The instruments in this study were interviews and observations conducted before and after the intervention. Statistical test results show the basic rate of return to the elderly before and given different interventions with a significant level of 0.017 (p <0.05). Based on the results of research that is supported so that further research can discuss further by using other confounding variables that can increase comfort and develop proper hip exercise stretching time.